First-line Immuno-chemotherapy for extensive-stage small-cell lung cancer: A network meta-analysis and cost-effectiveness analysis - Zhu, Youwen; Liu, Kun; Yang, Qiuping; Zeng, Manting; Peng, Libo (Frontiers in Public Health, 2023)
Introduction Many randomized controlled trials have indicated that immuno-chemotherapy could generate clinical benefits, though the cost of immuno-chemotherapy was so prohibitive and the options were varied. This investigation aimed at evaluating effectiveness, safety, and cost-effectiveness for immuno-chemotherapy as a first-line therapeutic option for ES-SCLC patients. Methods Multiple scientific literature repositories were searched for clinical studies where immuno-chemotherapy was regarded as the first-line treatment for ES-SCLC, which were published in English between Jan 1, 2000, and Nov 30, 2021. This study conducted a network meta-analysis (NMA) and cost-effectiveness analysis (CEA) based upon US-resident payer perspectives. Overall survival (OS), progression-free survival (PFS), and adverse events (AEs) were evaluated through NMA. In addition, costings, life-years (LYs), quality-adjusted life-years (QALYs), and incremental cost–benefit ratio (ICER) were estimated by CEA. Results We identified 200 relevant search records, of which four randomized controlled trials (RCTs) (2,793 patients) were included. NMA demonstrated that the effect of atezolizumab plus chemotherapy was ranked at a more elevated position in comparison to other immuno-chemotherapy options and chemotherapy alone, within the general population. The influence of atezolizumab plus chemotherapy and durvalumab plus chemotherapy was ranked higher within populations experiencing non-brain metastases (NBMs) andbrain metastases (BMs), respectively. The CEA revealed that the ICERs of immuno-chemotherapy over chemotherapyalone were higher than the willingness-to-pay (WTP) threshold of 150,000/QALY in any population. However, treatment with atezolizumab plus chemotherapy and durvalumab plus chemotherapy were more favorable health advantages than other immuno-chemotherapy regimens and chemotherapy alone, and the results were 1.02 QALYs and 0.89 QALYs within overall populations and populations with BMs, respectively. Conclusion The NMA and cost-effectiveness investigation demonstrated that atezolizumab plus chemotherapy could be an optimal first-line therapeutic option for ES-SCLC when compared with other immuno-chemotherapy regimens. Durvalumab plus chemotherapy is likely to be the most favorable first-line therapeutic option for ES-SCLC with BMs.